Bradyrhizobium spp. inoculation associated with nitrogen application enhances the quality of soybean seeds - Alan Mario Zuffo; Rafael Felippe Ratke; Jorge González Aguilera; Fábio Steiner (Ciência e Agrotecnologia, 2021)
ABSTRACT The physiological seed quality can be altered by nutritional management of the soybean crop, especially by the fertilization with nitrogen (N), which is a structural component of several organic compounds, including proteins, and has an important catalytic role in the activation of several enzymes. The aim of this research was to investigate the effects of sources and application rates of mineral N fertilizer associated with inoculation of Bradyrhizobium spp. on physiological quality of soybean seeds. The treatments were arranged in a completely randomized block design, in a 3 × 5 factorial arrangement [three N fertilizer sources (Bradyrhizobium spp. inoculation; Bradyrhizobium spp. inoculation + urea application; and, Bradyrhizobium spp. inoculation + ammonium sulfate application) and five N application rates (0, 50, 100, 150 and 200 kg N ha-1)], with four replicates. Nitrogen fertilizer was applied in topdressing at R2 stage when soybean plants were in full flowering. The quality parameters evaluated in soybean seeds were: 1,000-seed mass, seed protein content, germination, first germination count test, seedling emergence, emergence speed index, accelerated aging, electrical conductivity, vigor and viability of seeds by tetrazolium test. The application of 50 kg N ha-1 of mineral fertilizer (ammonium sulfate or urea) associated with the Bradyrhizobium spp. inoculation enhanced the physiological quality of soybean seeds, resulting in higher seed germination percentage and higher emergence and seedling emergence speed index. The application of ammonium sulfate or urea (50 kg N ha-1) at full flowering of soybean plants inoculated with Bradyrhizobium spp. can improve the physiological quality of soybean seeds.